Diversity oriented biosynthesis via accelerated evolution of modular gene clusters - Aleksandra Wlodek (Nature Portfolio, 2017)
Reengineering polyketide synthase encoding genes to produce analogues of natural products can be slow and low-yielding. Here the authors use accelerated evolution to recombine the gene cluster for rapid production of rapamycin-related products.